Mudanças e continuidades na elite parlamentar de Goiás: 1982-2010 - MOTA, Regys Rodrigues da (2011)
The goal of this research is to analyze the process of democratization of political elites observing changes and continuities in the profile of the parliamentarians in the composition of the Legislative Assembly of Goiás during the period 1982 to 2010.